Reality and challenges of child's rural education in the Paraense Amazon - Maria Natalina Mendes Freitas; Maria Izabel Alves dos Reis; Salomão Antônio Mufarrej Hage (Universidade Federal de Santa Catarina, 2019)
This article presents reflections on the reality and challenges of Child's Rural Education in the Paraense Amazon, resulting from studies being developed by the Group of Studies and Research in Rural Education in the Amazon (GEPERUAZ) in articulation with the Paraense Forum of Rural Education and the Observatory of Higher Rural Education. We aim with these studies to produce information on the attendance of the Child's Rural Education in the State and Municipalities of Pará, with the perspective of strengthening the struggles for the guarantee of the right to education at this school stage, as established by the country's educational legislation. Based on bibliographical and documentary analysis, providing statistical data, we began the article contextualizing the Amazonian territory and presenting reflections that refer to the challenges faced by Child Education in this territory. In the sequence, we highlight the attendance at this school stage by the municipalities of Pará and the pedagogical proposals that have been implemented, analyzing relevant aspects of the reality found. The results indicate the urgency and need to value children who live in the countryside and in the city, in the State of Pará, in the Amazon and in Brazil, and the implementation of public policies is crucial for this to take effect, especially in rural areas.